PENGARUH PERENCANAAN KARIR DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT CAT DI KOTA MALANG - Dovian Millian; Sudibyo Aji Narendra Buwana (Jurnal Manajerial, 2017)
In the world of work each organization or company to be a place where employees are working of course expected to provide good career for the life of the employee. Career planning and career development is also of course be a point which is of considerable concern and very important in a company or organization, both for the company and the employees themselves. Sources of data in the research were employees and HRD Manager at PT CAT by using random sampling techniques. The conclusion of the research is in the PT CAT are partial positive influence on career planning to employee performance and positive influence between motivation on employee performance as well as significant positive influence between career planning and motivation on employee performance.